Service oriented cross-platform framework for 3D part library based on diversiform knowledge implantation. Issue 6 (2nd November 2018) - Liu, Wei; Niu, Qiang; Kong, Chuipin; Zhou, Xionghui
ABSTRACT: Recent years have seen the great advancement in rapid design and manufacture. As a primary foundation, part libraries play an important role in machine and mold design. Most current libraries are created in specific use environments or CAD platform, which will bring obstacles in the share and exchange of part information. In this paper, we proposed a service oriented cross-platform framework for 3D part library, in which the parts in the library are created in a native ACIS modeler, and then the models are converted into CAD files with various formats, finally these files can be imported into CAD platform for practical design. The whole framework can be divided into three parts, namely, PLS(Part Library Service) provider, PLS adapter and PLS host. Through different adapters, the PLS can be easily grafted on most mainstream applications as a plug-in subsystem or even deployed on the website. In the detailed implementation, diversiform knowledge for part parameter and design is implanted to automatically define the geometry and rule constraints in the parts, with which the users can easily edit or customize the part library according to their needs. The PLS system has been applied in many manufacturing enterprises, and accumulates a large number of successful practical cases. GRAPHICAL ABSTRACT: